LEGAL PROTECTION FOR CREDITORS IN ENHANCING TRUST IN CREDIT AGREEMENTS WITH MORTGAGE RIGHTS AS COLLATERAL - Kurniawan, Itok Dwi; Septiningsih, Ismawati (Faculty of Law, Universitas Pekalongan, 2024)
Economic and business development in Indonesia heavily relies on the role of financial institutions, especially banking, in providing capital through credit facilities. However, credit distribution also carries the risk of default, necessitating an adequate legal protection system for creditors. This research aims to analyze the legal protection for creditors in credit agreements with mortgage rights as collateral under Indonesian positive law, identify issues hindering its implementation, and formulate solutions to strengthen legal protection to increase creditor confidence. The study employs a normative legal research method with conceptual and statutory approaches, focusing on an in-depth analysis of creditor protection in credit agreements with mortgage rights through examination of legal principles, legal systematics, and relevant legislation. Data collection is conducted through literature study, while data analysis uses a qualitative method with a deductive approach, involving stages of identification, interpretation, consistency analysis, and synthesis to identify legal gaps and formulate recommendations for improving legal protection for creditors. The research results reveal that legal protection for creditors in credit agreements with mortgage rights in Indonesia faces several obstacles, including ineffective execution processes, limited collateral objects, lack of certainty in collateral valuation, limited capacity of registration institutions, and low public legal awareness. To address these issues, proposed solutions include optimizing execution implementation, expanding collateral objects, creating clear valuation guidelines, enhancing the National Land Agency's capacity, providing legal education to the public, improving relevant regulations, increasing inter-agency coordination, and strengthening supervision and law enforcement. The implementation of these measures is expected to increase creditor confidence, improve the investment climate, and promote economic growth while maintaining a balance of interests among all parties.